Pathogenesis and heterogeneity of ovarian cancer. Issue 1 (February 2017) - Kroeger, Paul T.; Drapkin, Ronny
Abstract : Purpose of review: The most common type of ovarian cancer, high-grade serous ovarian carcinoma (HGSOC), was originally thought to develop from the ovarian surface epithelium. However, recent data suggest that the cells that undergo neoplastic transformation and give rise to the majority of HGSOC are from the fallopian tube. This development has impacted both translational research and clinical practice, revealing new opportunities for early detection, prevention, and treatment of ovarian cancer. Recent findings: Genomic studies indicate that approximately 50% of HGSOC are characterized by mutations in genes involved in the homologous recombination pathway of DNA repair, especially BRCA1 and BRCA2 . Clinical trials have demonstrated successful treatment of homologous recombination-defective cancers with poly-ribose polymerase inhibitors through synthetic lethality. Recently, amplification of CCNE1 was found to be another major factor in HGSOC tumorigenesis, accounting for approximately 20% of all cases. Interestingly, amplification of CCNE1 and mutation of homologous recombination repair genes are mutually exclusive in HGSOC. Summary: The fallopian tube secretory cell is the cell of origin for the majority of ovarian cancers. Although it remains unclear what triggers neoplastic transformation of these cells, certain tumors exhibit loss of BRCA function or amplification of CCNE1 . These alterations represent unique therapeutic opportunities in ovarian cancer.